The approaches to the assessment of biosimilarity of biotechnological preparations: quality issues - A. N. Mironov; V. A. Merkulov; A. I. Lutseva; O. A. Vaganova; A. A. Bendryshev; T. A. Efremova; E. V. Kirichenko; S. V. Shvets; E. V. Ivanainen (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Due to expiration of patents for most highly demanded biotechnological preparations there is a tendency for the increase in the number of applications for marketing authorisation of biosimilar preparations (biosimilars). In the Russian Federation, the process of bringing biosimilars to the market has just started. It should be expected that in the upcoming years the global tendency for brining biosimilars of previously authorized preparations will become real in Russia. In this regard there is a need for developing national requirements for drugs submitted for marketing authorization as biosimilars. In the present article the authors propose for consideration main approaches for selecting criteria for confirmation of biosimilarity in terms of their quality assessment and determining the amount of studies required to confirm the similarity and comparability of physical, chemical and biological properties of biosimilars in comparison with the originator.